Computer programming and novice programmers - Piteira, M.; Costa, C. (ISDOC '12: Proceedings of the Workshop on Information Systems and Design of Communication, 2012)
Computer Programming is one of the skills very useful and can be a very rewarding career. However teaching and learning of computer programming is referred as one of the disciplines that face great challenges. Drop out, unmotivated and high levels retention of student's in the first year are problems that is imperative to solve. Strategies implemented by educators to overcome this problem have been used. Some of them are based on technology. Educators introduce in the learning process tools to support and facilitate the learning of computer programming. This work identifies the main computer programming topics teach and learn in the first year of the computer education and the main difficulties felt by the novice programmers. The main contribution of this work is the identification of computer programming topics with a low and high level comprehension.